The Effect Of Eating Movement And Main Cutting Angle On The Result Of The Cylinders Of The Working Objects On The Cylindic Lathe Process - Nugroho, Adi (Sean Institute, 2023)
A quality product is obtained from good cutting conditions. One of the deviations caused by the cutting conditions is the cylindrical process of the process, therefore in this study the effect of the feed motion (f) and the main cutting angle (Kr) on the cylindrical results of the workpiece surface on the cylindrical lathe process was carried out. The machining process is carried out with a depth of cut of 0.5 mm by varying the feeding motion (f) and the main cutting angle (Kr) with a constant spindle rotation (n) of the ST 37 workpiece which has a diameter of 30 mm and a length of 150 mm and is turned along ± 120 cm. mm using an HSS chisel. After the workpiece is turned, the cylindrical size of the workpiece is measured using Block – V and Dial Indicator. The results of this study found that, in the use of Kr = 90° (β = 60°, = 3°, = 27°) cylindrical value = 180 – 390 m, Kr = 70° (β = 50°, = 13°, = 27°) cylindrical value = 370 - 480 m, and Kr = 60° (β = 34 °, = 24°, = 32°) the cylindrical value = 510 – 860 m. Feeding motion has a great influence on the cylindrical surface, because the greater the feeding motion, the greater the cylindrical value. This is due to the less cylindrical in the workpiece during the machining process. The main cutting angle (Kr) also has a big influence on the cylindrical surface, because the smaller Kr, the greater the cylindrical value. This is because the use of a small Kr is not profitable because it will reduce the geometric accuracy of the product, in this case it will also affect the cylindrical result and cause the workpiece to become non-cylindrical (the cylindrical size is getting bigger).